Prevalence of Anaemia among Pregnant Women Attending Benghazi Medical Centre - Elsaid, Amina; Alghoul, Amal; Sahanoun, Enas; Aiad, Enaam; Aldresi, Mohamed; Elfaitory, Anas (AlQalam Journal of Medical and Applied Sciences, 2025)
Anemia in pregnancy is a public health problem with poor outcomes for both mother and child. It is the most common cause of maternal mortality. Severe anemia is associated with preterm birth, low birth weight, and a fetus small for gestational age. Though anemia is an easily treatable and largely preventable disease if detected, it continues to be significantly prevalent among pregnant women. This study was conducted to assess the prevalence of anemia among pregnant women receiving care at the obstetric unit within Benghazi Medical Center. A cross-sectional study was conducted on 100 pregnant women randomly selected attending the Benghazi Medical Center -Benghazi, Libya. The prevalence of anemia was 71%. The higher prevalence of anemia was in the third trimester of pregnancy (91%). Anemia was more prevalent in pregnant women within the age of 29-39(51%) and with a university-level education (40%). Daily meat consumption was reported by 41% of the pregnant women. The majority of participants consumed green vegetables daily (75%), although fresh fruit consumption was infrequent for many (46%). Approximately 53% reported consuming 2-3 meals per day. Most pregnant women did not drink tea immediately after meals (63%). Approximately 81% of the participants reported taking iron, folic acid, and vitamin supplements. There is no statistical association between anemia and any characteristic of a pregnant woman. Our study concludes that the prevalence of anemia in pregnant women was 71%. Strengthen community health education about anemia in pregnancy, Health education should include the consequences of anemia in pregnancy, proper nutrition, maintaining regular antenatal visits, and the importance of early diagnosis of anemia.